PERBANDINGAN PENGGUNAAN KOSMETIKA EYEBROW GEL DAN EYEBROW CREAM TERHADAP HASIL PEMBENTUKAN ALIS TIPIS PADA RIAS WAJAH PENGANTIN BARAT - ANGGUN SURYA NINGSIH; Murni Astuti (Universitas Negeri Padang, 2022)
This study aims to compare the use of eyebrow gel and eyebrow cream cosmetics to the results of the formation of thin eyebrows in Western bridal make-up. This type of research is a quasi experiment. The research sample was 6 people. The data collection technique was purposive sampling. Descriptive data analysis techniques by displaying the mean, standard deviation, minimum, and maximum values. Bivariate analysis using independent-sample t-test with a confidence degree of 90%. The results of using eyebrow gel cosmetics for the results of the formation of thin eyebrows of West Pegantin found that the highest value was found in the favorite aspect, namely 3.19 having dislike criteria. In the use of eyebrow cream cosmetics, it was found that the highest value was in the neatness aspect, namely 3.52 having very neat criteria. There is a difference in the effect of using eyebrow gel and eyebrow cream cosmetics on the results of thin eyebrow formation in Western bridal make-up on the flatness aspect (p = 0.000), on the neatness aspect (p = 0.000), and on the favorite aspect (p = 0.000). The conclusion of this study is that there is an effect of using eyebrow gel and eyebrow cream cosmetics on the results of thin eyebrow formation in Western bridal make-up.